A Feminist Thucydides? - O'Sullivan, Rory (Histos, 2024)
This paper reconsiders the representation of women in Thucydides and the possibility for a feminist interpretation of the Peloponnesian War. It analyses three key passages where the representation of women is highly idealised and subverts the normal values depicted in the text. From there it proceeds to claim that in many places the Peloponnesian War offers a gendered and negative portrayal of masculine characters and values as they influence the war. This suggests the possibility of a Thucydides who is thinking about gender in terms very different from his characters and more like contemporaries such as Plato.